Changes in the medical burden of pyogenic and tuberculous spondylitis between 2007 and 2016: A nationwide cohort study. (March 2020) - Kim, Yeo Song; Kim, Jeong Gyun; Yi, Jeeeun; Choi, Jung Min; Chung, Chun Kee; Choi, Un Yong; Han, In-bo; Sohn, Seil
Highlights: A total of 9655 newly diagnosed patients with PS or TS were enrolled in 2007 and 2016 year. Among the 9655 subjects, the PS and TS groups consisted of 7305 and 2350, respectively. The total medical cost for the PS group increased significantly between 2007 and 2016 in Korea. The total medical cost for the TS group decreased between 2007 and 2016 in Korea. Abstract: Background: This nationwide study aimed to compare the medical burdens of pyogenic spondylitis (PS) and tuberculous spondylitis (TS) between 2007 and 2016 in Korea. Methods: We used a national database managed by the National Health Insurance Service (NHIS) with data from the years 2007 and 2016. A total of 9655 newly diagnosed patients with PS or TS were correspondingly enrolled in the PS or TS group. Chi square test analyses were used to compare the PS and TS groups. Results: The overall incidence of infectious spondylitis during the study period was 9655 persons. The PS and TS groups consisted of 7305 and 2350 cases, respectively. Individual medical costs in the PS group (USD 10, 049 ± 94 vs. USD 16, 672 ± 17, 729, P < 0.001) and the TS group (USD 4882 ± 6869 vs. USD 8531 ± 10, 709, P < 0.001) both increased. The total medical cost for the PS group increased significantly between 2007 and 2016 in Korea (USD 24, 428, 560 vs. USD 81, 044, 196, P < 0.001). In contrast, the total medical cost for the TS group decreased between 2007 and 2016 in Korea (USD 8, 573, 038 vs. USD 4, 879, 520, P < 0.001). Conclusion: This nationwide study shows that the total medical cost of PS has increased and that the total medical cost of TS has decreased between 2007 and 2016 in Korea.